An acid/base responsive side-chain polyrotaxane system with a fluorescent signal. Issue 10 (10th February 2016) - Cao, Zhan-Qi; Luan, Zhou-Lin; Zhang, Qi; Gu, Rui-Rui; Ren, Jun; Qu, Da-Hui
Abstract : A side-chain polyrotaxane system can generate a remarkable fluorescent signal change in response to acid/base stimuli. Abstract : An acid/base-responsive polyrotaxane system was constructed, in which the side chain was modified with a diferrocene-functionalized bistable rotaxane molecular switch via the "CuAAC" click reaction. The reversible subunit shuttling movement of the rotaxane unit in the polymer system in response to external acid/base stimuli was accompanied by visual fluorescence changes.